Balança comercial do Ceará no período de 2006 a 2011: uma análise do fluxo interestadual - Peixoto, Pedro Bezerra (2013)
With globalization have occurred in the last decade of the 20th century, several changes on the world stage. Given these changes in the foreign trade went through changes and the necessity of reformulating their strategies, countries diversify markets and implement international trade agreements. Under these perspectives, this work shows the trade performance of Ceará from 2006 to 2011, from the perspective of external and internal flow, with emphasis in the second, using data from the Secretariat of Finance of Ceará State. It was noted that transactions of foreign trade deficit of over the period reviewed, as well as Interstate Commerce, greater scope of this work. At work is the moving of operations around the main activities, in addition to the States largest buyers and sellers for Ceará.